Analisis Perbandingan Perhitungan PPh 21: Penerapan Skema Tarif Efektif Rata-Rata (TER) dengan Aturan Lama bagi Karyawan Tetap - Nawangsari, Nonny Laurencia; Widajantie, Tituk Diah (VISA: Journal of Vision and Ideas, 2024)
The calculation of Income Tax (PPh) Article 21 for permanent employees is often considered complicated and confusing, especially with the various calculation schemes available. This study aims to compare two PPh 21 calculation methods: the newly implemented Average Effective Rate (TER) scheme and the old rules, to identify the main differences between the two methods. A comparative method was chosen to analyze the theoretical review of the PPh 21 calculation methods, conduct calculation simulations with both methods, and evaluate their impact on the amount of tax payable by permanent employees. The main reason for writing this article is to provide a deeper understanding of the differences in PPh 21 calculations between the two methods and to offer recommendations to relevant parties, especially to enhance the understanding of students and tax practitioners regarding PPh 21 calculations. Thus, this article is expected to help reduce the confusion and administrative burden often faced by taxpayers in fulfilling their tax obligations. The results of this study show that the implementation of the TER scheme can simplify the PPh 21 calculation process and improve tax administration efficiency, although proper socialization and understanding are still required to optimize tax compliance.